Optimalisasi Kelompok Sadar Wisata (Pokdarwis) dalam Meningkatkan Pengunjung Pantai Gemah, Kabupaten Tulungagung Pasca Pandemi COVID-19 - Laily Purnawati; Fathul Qorib (Jurnal Ilmu Sosial dan Ilmu Politik)
Gemah Beach, a prominent tourism icon in Tulungagung, has gained popularity on social media and substantially contributes to both local and governmental revenue. However, the onset of the COVID-19 pandemic in 2019 led to a significant decline in visitor numbers, necessitating strategic development efforts to revive interest in the post-pandemic era. This study aims to analyze the policies and factors influencing visitor interest, as well as the role of the Tourism Awareness Group (Pokdarwis) in managing the beach. Data was collected through interviews, observation, and documentation, with the researcher serving as the primary instrument. The data was processed qualitatively using purposive sampling, and validity was ensured through interactive analysis techniques and triangulation. The findings reveal that Pokdarwis successfully increased visitor numbers post-pandemic by improving human resources, enhancing infrastructure, and promoting the beauty of Gemah Beach through trending social media campaigns.